Análise de projetos para reintegração social de presidiários no Estado de São Paulo, com base em critérios extraídos de uma literatura analítico comportamental - Guimarães, Thais Albernaz Machado do Carmo (2008)
The goal of our research was to apply the lessons of behavioral analysis to the Sao Paulo state policy regarding social reintegration of prison inmates. Our source data came from two official documents made available by the State: (1) The Monthly Following Report, and (2) the Manual of Projects of Social Reintegration (MPRS Manual de Projetos de Reintegração Social). The MPRS tracks guidelines for the development of government policies, and acted as the primary data source for our research. Our analysis asks a series of questions: towards what groups are these projects targeted? What behaviors they are hoping to remedy? What are their objectives? What are the procedures used to encourage specific behaviors and what resources are used? What is the relation between the program and the reality of life outside prison? What sort of evaluation has been done on these projects? What does this say about the state policy towards social reintegration of prisoners? The behavioral analysis literature suggests a series of elements that should be considered in planning a social program, and in dealing with intervention. This literature guided the organization of our research. The results evince a lack of valuable information in those projects guided by the MPRS, and for that reason the Manual was used more as a guide of missing elements than as an instrument of behavioral analysis. The difficultly of organizing the material is itself a reflection of the State s inability to deal with social reintegration of prisoners. The results of our research, and the high criminal relapse rates in the State of Sao Paul 40% highlight the deficiency of programs currently deployed in this area, and point to the need for a joint social, governmental and scientific effort to remedy the problem